Prognostic value, immune signature and molecular mechanisms of the APOBEC family members APOBEC1, APOBEC3A, APOBEC3G and APOBEC3H in pancreatic adenocarcinoma - Duan, Yunjie; Du, Yongxing; Gu, Zongting; Zheng, Xiaohao; Wang, Chengfeng (Frontiers in Molecular Biosciences, 2022)
Background: Increasing evidence supports that the APOBEC family is associated with development of a variety of cancers. However, the function of APOBEC1/3A/3G/3H in PAAD is still unclear. Methods: Comprehensive bioinformatic analysis using R (version 3.6.3), TISIDB, Metascape etc. were performed to study the clinicopathological characteristics, prognostic value, immune features and functional mechanisms of the APOBEC1/3A/3G/3H in PAAD. Results: APOBEC1/3A/3G/3H showed significantly elevated expression in PAAD than para-cancerous or normal tissues. Their high expression or amplification were significantly correlated with worse clinicopathological characteristics and prognosis in PAAD patients. In addition, the role of APOBEC1/3A/3G/3H in the immune regulation is diverse and complex, the high expression of APOBEC1 may inhibit the infiltration level of many kinds of immunoreactive tumor-infiltrating cells, which may be an important factor leading to immune escape of PAAD cells. Mechanistically, APOBEC1/3A/3G/3H played an activating role in multiple oncogenic pathways, including the EMT, RAS/MAPK and TSC/mTOR pathways. Moreover, we found that the expression level of APOBEC3G was positively correlated with the sensitivity of gemcitabine and doxorubicin. Conclusion: APOBEC1/3A/3G/3H play an oncogenic role in the development of PAAD and might serve as new biomarkers or therapeutic targets.